Comparative growth kinetics and drug susceptibility of Mycobacterium tuberculosis lineages prevalent in Ethiopia: implications for tuberculosis treatment and management - Hailemariam, Tesfaye Gebreyohannis; Tilahun, Melaku; Atnafu, Abay; Gelanew, Tesfaye; Gebresilase, Tewodros Tariku; Tola, Mekdes Alemu; Ayele, Abaysew; Siraj, Shewki Moga; Shibeshi, Workineh; Bobosha, Kidist; Wassie, Liya; Hirutu, Yonas; et al. (Frontiers in Microbiology, 2025)
Tuberculosis (TB) remains a global health challenge, with treatment outcomes influenced by the genetic diversity of Mycobacterium tuberculosis (Mtb) strains. This study examines the growth kinetics and drug susceptibility of Mtb strains from different lineages in Ethiopia to understand their impact on disease management. Mtb strains, including sub-lineages 4.1.2.1, 4.2.2.2, 4.6.3, lineages 3 and 7, and the reference strain H37Rv (ATCC 27294), were cultured in liquid 7H9 Middlebrook broth. Growth began on day 6 post-inoculation. Sub-lineage 4.1.2.1 showed rapid exponential growth by day 9, reaching the stationary phase by day 15. Sub-lineage 4.1.2.1 followed by sub-lineage 4.2.2.2 had the highest maximum growth concentration (Cmax), indicating enhanced growth efficiency and adaptive traits that may increase their pathogenicity or resistance to host defenses or anti-TB drugs. To support this observation, the minimum inhibitory concentrations (MIC) for first-line anti-TB drugs were assessed for all the studied Mtb strains using the microdilution broth method. While all strains were susceptible, MIC values varied. Sub-lineages 4.1.2.1 and 4.2.2.2 had MIC values matching WHO’s critical concentrations (except for rifampicin). Lineage 3 showed increased sensitivity to rifampicin, isoniazid, and streptomycin, requiring only half the standard concentration. Lineage 7 also exhibited higher sensitivity to rifampicin and streptomycin. These findings highlight the importance of considering lineage-specific differences in Mtb strains for optimizing treatment regimens and improving TB control strategies, particularly in regions with diverse Mtb populations like Ethiopia.